Three Dimensional Detection of the via in the PCB CT Image Using Morphology Operation - Li, Han Ning; Jia, Tao; Chen, Jian; Yan, Bin; Xu, Yi Fu; Li, Zhong Guo; Zeng, Lei (Applied Mechanics and Materials, 2015)
In modern industry, the nondestructive testing of printed circuit board (PCB) can prevent effectively the system failure and is becoming more and more important. As a vital part of the PCB, the via connects the devices, the components and the wires and plays a very important role for the connection of the circuits. With the development of testing technology, the nondestructive testing of the via extends from two dimension to three dimension in recent years. This paper proposes a three dimensional detection algorithm using morphology method to test the via. The proposed algorithm takes full advantage of the three dimensional structure and shape information of the via. We have used the proposed method to detect via from PCB images with different size and quality, and found the detection performances to be very encouraging.